Immunological and biological evidence for a stanniocalcin-like hormone in human kidney. - Wagner, G F (1995)
The corpuscles of Stannius are responsible for the synthesis and secretion of stanniocalcin (STC), a glycoprotein hormone that regulates calcium and phosphate homeostasis in fishes through its actions on the gills and kidneys. The corpuscles of Stannius and STC are considered to be an endocrine system that is unique to fishes. In this report, we provide evidence for the existence of STC-like proteins in vertebrates other than fishes, in particular, humans. By using a well-characterized RIA for salmon STC, sera from vertebrates as diverse as sharks and humans contained measurable levels of STC-like immunoreactivity in the concentration range commonly observed in fishes, and all of these sera exhibited parallelism in the assay. By using Western blot analysis, proteins were also identified in human kidney extracts that shared several properties with the fish hormone in addition to their cross-reactivity with salmon STC antiserum. The same antiserum was used to identify a discrete population of cells in human kidney tubules that could be the source of serum immunoreactivity. Human kidney extracts containing the STC-immunoreactive proteins also had STC-related effects when injected into fishes. Collectively, the data suggest that STC may be more widespread among the vertebrates than is currently accepted.